2020
DOI: 10.3847/1538-3881/ab5f0b
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Blue Straggler Population of the Old Open Cluster Collinder 261

Abstract: Blue stragglers (BSs) are stars located in an unexpected region of the color-magnitude diagram (CMD) of a stellar population, as they appear bluer and more luminous than the stars in the turn-off region. They are ubiquitous, since they have been found among Milky Way field stars, in open and globular clusters, and also in other galaxies of the Local Group. Here we present a study on the BS population of the old and metal-rich open cluster Collinder 261, based on Gaia DR2 data and on a multi-epoch radial veloci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…The CMDs of the clusters have been very useful tool in identification of the member stars and determination of the cluster parameters. These are also used in the study of blue stragglers, rotation of stars, and multi-population in the clusters (Cordoni et al 2018;Piatti & Bonatto 2019;Rain et al 2020). In this study we used (B-V)/V CMDs to derive age of the clusters.…”
Section: Age Through Cmdmentioning
confidence: 99%
“…The CMDs of the clusters have been very useful tool in identification of the member stars and determination of the cluster parameters. These are also used in the study of blue stragglers, rotation of stars, and multi-population in the clusters (Cordoni et al 2018;Piatti & Bonatto 2019;Rain et al 2020). In this study we used (B-V)/V CMDs to derive age of the clusters.…”
Section: Age Through Cmdmentioning
confidence: 99%
“…For Berkeley 17, the BSS distribution was found to be similar to the family II globular clusters (Bhattacharya et al 2019). Rain et al (2020) found a flat distribution (family I) for Collinder 261.…”
Section: The Bss Of King 11mentioning
confidence: 77%
“…Using the WIYN data from the WOCS collaboration (see Mathieu & WOCS Collaboration (2013), for example, for more details) would be ideal for this experiment, since it focuses on old open clusters and, at least for clusters like NGC 188, M67 and a few others, extensive studies have been done over the last several decades to thoroughly quantify the issue of cluster membership, and even provide BS binary fractions in some clusters (e.g. Mathieu & Geller 2009;Rain et al 2020). In order to increase the sample size for the number of clusters with known BS binary fractions, these WIYN data can be combined with the GC data coming from double BS sequences.…”
Section: Blue Stragglersmentioning
confidence: 99%